2003
DOI: 10.1348/014466603322595266
|View full text |Cite
|
Sign up to set email alerts
|

I feel for us: The impact of categorization and identification on emotions and action tendencies

Abstract: Building upon the social emotion model (Smith, 1999), we examined the combined impact of categorization context and social identification on emotional reactions and behavioural tendencies of people confronted with the victims of harmful behaviour. Depending on conditions, participants were led to categorize the victims and themselves in the same common group or in two distinct subgroups of the larger common group. We also measured participants' level of identification with the group that was made contextually … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
213
1
4

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 273 publications
(236 citation statements)
references
References 27 publications
(32 reference statements)
18
213
1
4
Order By: Relevance
“…As previously observed (Mackie et al, 2000;van Zomeren et al, 2004;Yzerbyt et al, 2003), anger was the prominent emotion reported following discrimination, and such self-reported feelings were associated with greater endorsements of confrontational actions. However, priming anger itself did not augment such a response.…”
Section: Discussionsupporting
confidence: 75%
See 4 more Smart Citations
“…As previously observed (Mackie et al, 2000;van Zomeren et al, 2004;Yzerbyt et al, 2003), anger was the prominent emotion reported following discrimination, and such self-reported feelings were associated with greater endorsements of confrontational actions. However, priming anger itself did not augment such a response.…”
Section: Discussionsupporting
confidence: 75%
“…Although both shame and anger were evident under conditions of discrimination, other emotions might also be elicited that influence subsequent responses. For example, in some situations of discrimination, fear was exhibited and was associated with a lower likelihood of confrontational action (Woodzicka & LaFrance, 2001;Yzerbyt et al, 2003;but cf. Mackie et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations